Women in Decision-making: Investigating Roles and Challenges in Selected Governmental Offices at Hosanna City Administration - Tsehay, Yihenew Misrak (Ethiopian Journal of Social Sciences, 2021)
The process of decision-making affects both organization’s administration and the lives of the society. Accordingly, this study has been conducted to examine the roles of women participation in decisionmaking and to investigate challenges on their participation. The study employed qualitative method. Whereas participants of the study were selected purposively, data were collected through interviews and analysed thematically. The study showed that interest articulation, building institutional trust and socialization, proper utilization and management of resources, enhancing the achievement of institutional goals, upholding institutional responsibilities, making rational decisions and fighting maladministration are important contributions of women in decision-making. On the other hand, the overburden of women, low access for leadership positions, backward socio-cultural attitudes and practices, lack of trust at household level and feeling of discrimination, feeling of inefficacy and lack of motivation, low educational status and insufficient institutional support were the main challenges on women’s decision-making activity. Therefore, appreciating women’s role in decision-making activities and working to ease up their challenges must be the timely actions of all concerned parties.